CT Arterioportography for Complex Portomesenteric Venous Interventions - Kausthubh Hegde; Patrick D. Sutphin; Zubin Irani; Sanjeeva P. Kalva (Journal of Clinical Interventional Radiology ISVIR)
Authors report the use of computed tomography arterioportography (CTAP) in the diagnosis and endovascular treatment of portomesenteric venous occlusion. Three patients (2 male and 1 female; median age: 51 years) with an extrahepatic portal or mesenteric venous occlusion and variceal bleeding were included in this institutional review boards-approved retrospective study. CTAP was performed with an angiographic catheter positioned in the proximal superior mesenteric artery, and CT was obtained during the venous phase following the intra-arterial injection of contrast material. CTAP provided excellent opacification and delineation of portomesenteric veins, including occlusion length, intravascular webs, venous collaterals, and bleeding varices. This enabled preoperative planning for complex recanalization or extra-anatomic bypass to treat extrahepatic portal and mesenteric venous obstruction. There were no complications related to CTAP.